Combined Electrocoagulation and Ozonation for Color, TSS, and COD Removal from Batik Wastewater - Anggie Devitasari; Firra Rosariawari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The research was carried out in two stages. First, the electrocoagulation process was performed using aluminium electrodes with electric current settings of 1, 2, 3, 4, and 5 amperes and contact times of 20, 30, 40, 50, and 60 minutes. Second, the ozonation process was conducted with contact time variations of 0, 15, 30, 45, and 60 minutes. The analysed parameters were TSS, COD, and colour, and the data were further evaluated using ANOVA to determine the statistical significance of the treatment factors. The combination of electrocoagulation and ozonation demonstrates significant potential as an alternative method for reducing pollutant load in batik wastewater, particularly by lowering Total Suspended Solids (TSS), Chemical Oxygen Demand (COD), and colour. The electrocoagulation process achieved 98% TSS reduction and 67% COD reduction. Subsequently, ozonation further enhanced treatment efficiency, resulting in an impressive 93% reduction in COD and 37% reduction in colour. These promising results highlight the combined method's capability to support more environmentally friendly wastewater treatment efforts. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production